Kynurenine to tryptophan ratio as a biomarker of acute stress in fish. (February 2022) - Wish, Jade; Bulloch, Patrique; Oswald, Lisa; Halldorson, Thor; Raine, Jason C.; Jamshed, Laiba; Marvin, Chris; Thomas, Philippe J.; Holloway, Alison C.; Tomy, Gregg T.
Abstract: The aim of this study was to determine the kynurenine (KYN) to tryptophan (TRP) ratio (KTR) in fish tissue to assess its usefulness as a biomarker of acute stress. Laboratory held rainbow trout ( Oncorhynchus mykiss ) were subjected to an acute stressor and KYN, TRP and cortisol were measured in liver and brain tissues at 4- and 48-h post-stress. The analytical method used to determine our analytes was based on lyophilization, and liquid-solid extraction followed by isotope dilution high-performance liquid chromatography positive ion electrospray tandem mass spectrometry. The [KYN]/[TRP] ratio (KTR) was greater in fish liver and brain in the 48-h post -stress exposure group ( n = 8 ) relative to controls ( n = 8, p < 0.05); a similar increase was not observed in fish in the 4-h post-stress exposure group. Hepatic and brain cortisol levels were also elevated in fish from both stress-induced groups relative to their respective controls implying that cortisol responded more quickly to the stressful stimulus than KYN and TRP. Our results suggest that the KTR is a promising acute stress diagnostic biomarker in fish. Efforts are ongoing to assess whether the KTR can be used as a biomarker for chronic stress in fish exposed to aquatic contaminants and other environmental stressors and if similar assessments can be made on tissues collected via non-lethal approaches. Graphical abstract: Image 1 Highlights: Kynurenine to tryptophan ratio is a useful biomarker of acute stress in fish. Liquid solid extraction of visceral tissues was used to isolate amino acids. Detection and quantitation of analytes was done using LC/MS/MS.